Student’s Needs Towards Speaking Materials In Students’ Book For The First Year Of SMA Swasta Xaverius Gunungsitoli In 2023/2024 - Telaumbanua, Elfin Kurnia; Yasminar Amaerita Telaumbanua; Kristof Marthin Efori Telaumbanua; Nursayani Maruao (LPPM Universitas HKBP Nommensen, 2024)
This study aims to analyzing of the students’ needs towards speaking materials in students’ book for the first year of SMA Swasta Xaverius Gunungsitoli. To conduct this research, the researcher using a narrative method with a qualitative approach. Data were collected through interview and field note techniques. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results of the research study show that students' needs are : 1. Dialogue. Dialogue is : students need practice for conversation. 2. Vocabulary. Vocabulary is : Students need a wide and specific vocabulary to be able to speak fluently and effectively. 3. Grammar. Grammar is : Students need to understand correct and effective sentence structure to convey messages clearly. 4. Pronunciation. Pronunciation is : Proper pronunciation is very important to be understood by the listener. The researcher concluded that students' needs for speaking materials in English books are very important to be considered in the learning process. Proper needs analysis and relevant textbooks can help students to develop their speaking skills effectively.